PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII 1 JURUSAN TKJ SMKS NUR ILHAM PINGGIR - Yanti, Yasmi Devi; Suhermi, Suhermi; Kartini, Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aims to repair process learning and improve mathematics learning outcomes in grade XII technological computer and networking in vocational high school nur ilham district of Pinggir by implementing Cooperative Learning Model STAD type. Subjects of the research were 18 students grade XII whohave the academic ability of the heterogenous. This research is aclasroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM and of each cycle compared to the number of students who achieve KKM on base score. Results of this research indicate that the application of Cooperatif Learning Model STAD Type can repair process learning and improve the mathematics learning outcomes of students grade XII technological computer and networking in vocational high school nur ilham district of pinggir in the fifth semester academic year 2013/2014.Key words : Process Learning, Mathematics Learning Outcome, Cooperative Learning, STAD, Classroom Action Research.